Assessing the unmet need for modern contraceptives among reproductive-aged women in rural Nepal - Samyukta Chand; Kanittha Chamroonsawasdi; Paranee Vatanasomboon; Natkamol Chansatitporn (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this research was to determine the extent of the unmet need for modern contraceptives (MC) and its associated factors. Design/methodology/approach - This community-based cross-sectional survey was conducted via interview among 306 women. Percentages, means, standard deviations, Chi-square tests and multiple logistic regression were completed for data analysis. Findings - In total, 46.7% of respondents had total unmet need (24.8% spacing and 21.9% limiting). Multiple logistic regression for spacing showed the number of living children (AOR = 40.893, 95% CI = 6.930-241.292), no previous experience of MC (AOR = 30.149, 95% CI = 11.572-78.548) and level of knowledge (AOR = 5.587, 95% CI = 1.366-22.851). With regard to limiting pregnancies, respondent's age (AOR = 12.470, 95% CI = 1.264-86.734), number of living children (AOR = 21.257, 95% CI = 4.825-93.639) and no previous experience of MC (AOR = 120.542, 95% CI = 31.044-486.062) were recorded. Findings revealed that no previous experience of MC (AOR = 714.511, 95% CI = 160.646-3177.955) was a significant predictor of total unmet need. Originality/value - Experience and knowledge of MC play a vital role in the unmet need of MC use. A comprehensive education program to promote decision-making on MC choice and integrated family planning services at local communities by capacity building of service providers should be scaled up.